2020
DOI: 10.1584/jpestics.d20-011
|View full text |Cite
|
Sign up to set email alerts
|

Field survey of ryanodine receptor mutations (G4946E and I4790K) and their effects on biotic performance in the diamondback moth

Abstract: This study examined changes in the proportions of ryanodine receptor mutations (G4946E and I4790K) for Plutella xylostella populations in the field. Results show that the proportion of G4946E decreased during the survey years without diamide application and that insects with I4790K were observed less frequently during the survey period. This study also examined the biotic performances of diamide-resistant P. xylostella strains. The results show that the diamide-resistant strains exhibited hatchability, larval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…No detrimental impact associated with I4790M was observed on fecundity and fertility, in line with recent studies that examined the biotic performances of diamide-resistant P. xylostella laboratory-introgressed 28 and field-collected strains. 33,34 The results published therein showed that the diamide-resistant strains carrying G4946E or I4790K mutations exhibited hatchability, larval development and fecundity equivalent to those of diamide-susceptible strains.…”
Section: I4790m-mediated Resistance May Have a Costmentioning
confidence: 99%
“…No detrimental impact associated with I4790M was observed on fecundity and fertility, in line with recent studies that examined the biotic performances of diamide-resistant P. xylostella laboratory-introgressed 28 and field-collected strains. 33,34 The results published therein showed that the diamide-resistant strains carrying G4946E or I4790K mutations exhibited hatchability, larval development and fecundity equivalent to those of diamide-susceptible strains.…”
Section: I4790m-mediated Resistance May Have a Costmentioning
confidence: 99%
“…These sodium channel mutations have been widely detected in DBM populations in Australia, China, Korea, Thailand and Japan. The mutations I4790K/M, G4946E, E1338D and Q4594L were identified in the ryanodine receptor (RyR), conferring high resistance to the chlorantraniliprole in DBM 57–60 . The glutamate‐gated chloride channel (GluCl) is present only in invertebrates and is the main target gene of abamectin.…”
Section: Methodsmentioning
confidence: 99%
“…The mutations I4790K/M, G4946E, E1338D and Q4594L were identified in the ryanodine receptor (RyR), conferring high resistance to the chlorantraniliprole in DBM. [57][58][59][60] The glutamate-gated chloride channel (GluCl) is present only in invertebrates and is the main target gene of abamectin. The A309V substitution at the N terminus of the third transmembrane helix (M3) of the GluCl of DBM was identified in the resistant strain.…”
Section: Target Resistance Mutationsmentioning
confidence: 99%
“…7,13 The another resistance-associated RyR amino acid substitution, I4790M, was first identified in a Chinese population of P. xylostella, 14 and then homologous point mutations to PxRyR I4790M were found in some diamide-resistant field populations of T. absoluta RyR (I4746M/T), 12 C. suppressalis (I4758M), 13 S. frugiperda (I4734M), 8 S. exigua (I4743M) 15 and Orius laevigatus (I4790M). 16 Recently, I4790K mutation was found to confer high levels of resistance to diamides in some field populations of P. xylostella from Japan, China and Australia, [17][18][19] and of S. frugiperda from Brazil. 20 Compared to intensive investigations on target-site resistance of diamides, the role and molecular mechanisms of metabolic resistance to the diamide insecticides in insects is less studied and not clearly understood.…”
Section: Introductionmentioning
confidence: 99%